NUMERICAL MODELING OF ROCK DEFORMATION DURING COMPRESSION - Lin'kov A.M.; Dobroskok A.A. (My University, 2001)
Methodology of automatic tracking of trajectories of cracks has been offered. The methodology has been ground and is suitable for quantitative investigation of growth of cracks and deformation of rocks during compression. Mathematical models of processes in the rocks have been developed. Method of complex boundary elements has been applied during the investigations. Various hypotheses have been discussed. Error of using the hypotheses simplifying the models of investigated processes has been evaluated in case of isolated cracks. Behavior of crack systems has also been discussed. Role of the systems in variation of medium properties has been described.